The role of spatial texture in visual control of bumblebee learning flights - Linander, Nellie (J Comp Physiol A Neuroethol Sens Neural Behav Physiol, 2018)
When leaving the nest for the first time, bees and wasps perform elaborate learning flights, during which the location of the nest is memorised. These flights are characterised by a succession of arcs or loops of increasing radius centred around the nest, with an incremental increase in ground speed, which requires precise control of the flight manoeuvres by the insect. Here, we investigated the role of optic flow cues in the control of learning flights by manipulating spatial texture in the ventral and panoramic visual field. We measured height, lateral displacement relative to the nest and ground speed during learning flights in bumblebees when ventral and panoramic optic flow cues were present or minimised, or features of the ground texture varied in size. Our observations show that ventral optic flow cues were required for the smooth execution of learning flights. We also found that bumblebees adjusted their flight height in response to variations of the visual texture on the ground. However, the presence or absence of panoramic optic flow did not have a substantial effect on flight performance. Our findings suggest that bumblebees mainly rely on optic flow information from the ventral visual field to control their learning flights. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00359-018-1274-0) contains supplementary material, which is available to authorized users.